Farmers' Perceptions of the Competence of Agricultural Instructors in Karang Sidemen Village - Arifuddin Sahidu; Hayati Hayati; Muktasam Muktasam; Niechi Valentino; Muhammad Anwar Hadi (Postgraduate, University of Mataram, 2023)
Extension workers have a big role in the success of farming activities in an area and can indirectly have a big influence on the welfare of farmers in particular and the success of agricultural activities in general. The aim of carrying out this research is to describe the relationship between farmers' perceptions of the competency of agricultural instructors and at the same time determine the variables that influence farmers' perceptions of the competency of agricultural instructors in terms of farmer characteristics, farming business characteristics and the quality of extension. This research uses an exploratory descriptive approach with a survey method using interviews and the help of questionnaires. The sample was determined by quota sampling, namely 4 people in each agricultural farmer group consisting of the chairman and active members. Data are presented on a Likert scale, and relationship analysis uses the Rank Spearman statistical test. The results of the analysis of respondents' perceptions of instructor competence in terms of personality (2.87), andragogic (2.60), professional (2.63), and social (2.64) variables were at medium criteria (2-3). The relationship between each variable of personal characteristics, farming characteristics, and quality of extension with respondents' perceptions of PPL competency shows a real relationship with the variables of farming experience, land area, market accessibility, land ownership status, extension materials, extension methods, and extension media, where The extension method and extension material variables have the highest correlation coefficient among the others, namely (0.642) and (0.513) which are classified as a strong relationship level (0.51-0.75) at a confidence level of 0.01%.